VALUES FROM AN ANTAGONIST: ERIK’S FAVORABLE CHARACTERS FROM LEROUX’S THE PHANTOM OF THE OPERA - Suwastini, Ni Komang Arie; Pratama, Putu Yoga Sathya (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
The present study aimed at analyzing round and dynamic characters to look into the various dimensions of the antagonist in Gaston Leroux's The Phantom of the Opera and to reveal positive characterizations of an antagonist who is otherwise condemned as inherently evil due to its narrative function. The research was done under textual analysis employing McKee's (2003) as the grounded research design. The data were obtained from Gaston Leroux's Novel (1910), The Phantom of the Opera, in which Erik, the main antagonist, was focused the most. The data were gathered through some instruments, including notes and a table of classifications. The present study figures out some of the antagonist’s favorable characterizations even when he lived in difficult situations: talented singer, skillful entertainer, tenacious songwriter, and faithful lover. These findings imply that favorable values can be obtained even from the antagonists, rendering readers to be more critical in judging characters.